Peasants as Traditional Communities and Socio-Environmental Protection in a Mining Context: Constitutional and Infraconstitutional Analysis and a Case Study of the Pau Ferro Village (Craíbas/AL) (REMUNOM, 2026)
This article discusses the possibility of recognizing peasant communities as traditional peoples and communities, taking as reference the constitutional framework established in 1988 and the related infra-constitutional legislation, with emphasis on the National Policy for the Sustainable Development of Traditional Peoples and Communities (PNPCT). It is based on the premise that the Federal Constitution does not establish a closed list of protected collective subjects, while it safeguards cultural rights and both tangible and intangible cultural heritage (arts. 215 and 216), allowing for an open and inclusive interpretation of the ways of life that participate in the national civilizational process. Based on qualitative socio-legal research, which combines normative analysis and a case study, the situation of the Pau Ferro Village, in the municipality of Craíbas, Alagoas, is examined. This rural community is characterized by family farming, community networks, and religious practices that structure its social reproduction. The article demonstrates that the central criteria of traditionality (territoriality, knowledge transmitted through tradition, and specific forms of social organization) are present in the peasant way of life and are directly challenged by the implementation of the Serrote da Laje Project (Vale Verde Mining Company – hereinafter MVV), producing material, sanitary, psychosocial, and cultural damages, including reports of a desire for collective relocation. It concludes that framing the peasantry as a traditional community is legally defensible and relevant for qualifying the debate on environmental licensing, public participation, and full reparation in contexts of socio-environmental conflicts.